Pathogenic and genetic diversity of Fusarium oxysporum f. sp. ciceri isolates causing wilt disease in chickpea - KHAN, MUDASSER AHMED; GANGOPADHYAY, SAMIRAN; SHARMA, RAMAVTAR; SINGH, SHALANDRA (The Indian Journal of Agricultural Sciences, 2015)
An experiment was conducted to study pathogenic and genetic the variability of ten isolates of F. oxysporum f. sp. ciceri (FOC) using six chickpea genotypes and six RAPD markers. The F. oxysporum f. sp. ciceri isolates P-12, B-2 and BKN-1 proved to be most virulent to cause wilt disease in chickpea genotypes. These isolates were categorized based on mean wilt incidence into three groups: Group- I Highly virulent (P-12, B-2, BKN-1, FOC-1, S-13 and S-14), Group-II Moderately virulent (N-11 and J-7) and Group-III - Less virulent (D-3636 and U-549). Genetic diversity of F. oxysporum f. sp. Ciceri isolates examined for RAPD analysis revealed that the average number of polymorphic bands per primer were 7.83. The range of genetic similarity was found 0.79 (BKN-1 and FOC-1) to 0.10 (N-11 and B- 2). The average genetic similarity coefficient observed was 0.31 ±.